Analisis Tekuk Probabilistik Pada Batang Tekan dari Baja Ringan - Oktavia, Tuti; Sukamdo, Pariatmono (Universitas Mercu Buana, 2024)
Lightweight steel profiles have relatively thin thickness dimensions with the ratio of the dimensions of the width of each profile element to the thickness is very large, making it prone to bending. In SNI 8399:2017, mentions tolerances for geometric imperfections Bow (bw) (in the perpendicular direction Z-Z), Twist (h) (X-X direction), Camber, profiles C, Z, U. SNI 8399: 2017 has not been explained what kind of decrease in column strength against these geometric imperfections. In this study, an analogy was made to the measurement of imperfections in the geometry of the decapitated cone plate conducted by Pariatmono, 1994. In Pariatmono's research, data from the circular axis was changed into a horizontal axis by taking several angles in a circle, in this study it was taken every 6º (60 data in one row) and used as data with probablistic behavior. Then from the 60 rods obtained, Fourier analysis was carried out to obtain geometric imperfection equations. From these 60 bars obtained each Fourier coefficient. Then the average is taken, averaging +10%, +20%, +30%, +40%, +50% and -10%, -20%, -30%, -40% and -50% of the standard deviation values. Of the 11 rods, a non-linear buckling analysis was carried out using ANSYS Workbench 2022 R1. The probabilistic compressive analysis of geometric imperfections conducted in this study has not been able to definitively provide a general idea of the limits of geometric imperfections.